Endothelial Heterogeneity in Development and Wound Healing - David B. Gurevich (Cells, 2021)
The vasculature is comprised of endothelial cells that are heterogeneous in nature. From tissue resident progenitors to mature differentiated endothelial cells, the diversity of these populations allows for the formation, maintenance, and regeneration of the vascular system in development and disease, particularly during situations of wound healing. Additionally, the de-differentiation and plasticity of different endothelial cells, especially their capacity to undergo endothelial to mesenchymal transition, has also garnered significant interest due to its implication in disease progression, with emphasis on scarring and fibrosis. In this review, we will pinpoint the seminal discoveries defining the phenotype and mechanisms of endothelial heterogeneity in development and disease, with a specific focus only on wound healing.